HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP SUAMI DENGAN KEPATUHAN IBU DALAM PEMERIKSAAN KEHAMILAN TRIMESTER PERTAMA DI KLINIK BPM IKA NAGEZATARA KECAMATAN TIMANG GAJAH KABUPATEN BENER MERIAH - Darita, Syahfitri; HS, Nurlaely (Akper Kesdam I/Bukit Barisan Padang, 2025)
ABSTRACT Pregnancy heck-ups/antenatal care (ANC) that are carried out regularly and routinely is the most appropriate and important way to monitor and support the health of normal pregnant women and detect with normal pregnancies, pregnant women should visit midwives, doctors as early as possible since they feel they are pregnant to get antenatal care services/care. This study aims to analyze the relationship between husband's knowledge and attitude and mother's compliance in the first trimester at the BPM IKA Nagezatara Clinic, Timang Gajah District, Bener Meriah District, Aceh Province. The type of quantitative research with analytical descriptive research and research design uses a crosectional design approach. The total population of BPM IKA is 53 pregnant people. The total population of BPM IKA is 53 pregnant women. The determination of the sample amounted to 53. Based on the results of the chi square statistical test and at the level of 95% confidence was carried out to determine the relationship between the husband's knowledge and attitude and the mother's compliance in the first trimester at the BPM IKA Nagezatara Clinic, a p value of 0.781 (p ≥ 0.05) was obtained. Keywords : Knowledge, Husband's Attitude, Mother's Obedience